Phrenotomy for newborn patients with ankyloglossia: Integrative review (Research, Society and Development, 2023)
The aim of the present study focuses on presenting frenotomy as a therapeutic approach in the face of ankyloglossia in newborn patients and the benefits observed after performing the procedure. This is an integrative literature review. The inclusion criteria were applied to those articles that contemplated the proposed objectives, published between 2013 and 2023, in Portuguese and English and that dealt with the theme. As exclusion criteria, studies in editorial formats, studies in the format of letters to the editor, articles of integrative reviews or literature reviews, monographs, dissertations, theses and abstracts of annals were adopted. The searches resulted in a total of 466 articles that were indexed in the aforementioned scientific databases, of which 28 were in Bireme, 39 in Lilacs and 399 in PubMed. Among the identified studies, a quantitative of 13 studies were selected, 2 from Bireme, 4 from Lilacs and 7 from PubMed. During the analysis of the studies, it was identified that 54% of the studies were published between 2020 and 2023, despite the annual filter being applied to the last decade. In addition to the above, the majority of studies published by PubMed were observed in the selection, as well as the significant presence of studies associated with the journal: International journal of pediatric otorhinolaryngology. It is relevant to state that frenotomy may be a viable option to improve breastfeeding in cases of ankyloglossia and restrictive labial frenulum. However, it is necessary to carefully consider each individual situation, evaluate the long-term results and adopt a comprehensive and collaborative approach to ensure the effectiveness and safety of the procedure.